2005
DOI: 10.1016/j.ijsolstr.2004.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental dynamic characteristics of thin-film membranes

Abstract: Presented is a total-Lagrangian displacement-based non-linear finite-element model of thin-film membranes for static and dynamic large-displacement analyses. The membrane theory fully accounts for geometric non-linearities. Fully non-linear static analysis followed by linear modal analysis is performed for an inflated circular cylindrical Kapton membrane tube under different pressures, and for a rectangular membrane under different tension loads at four comers. Finiteelement results show that shell modes domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The majority of research in this area has focused on vibrations of nearly rigid elastic materials. Young et al (2005), for example, excite rectangular and cylindrical Kapton membranes by means of a shaker, and the resulting vibrations and mode shapes are captured using a scanning laser vibrometer. One of the difficulties of conducting dynamic inflation experiments with hyperelastic membranes is the ability to measure the deformation during inflation, as it requires recording displacement data for enough points and with sufficient sampling rates to capture the entire motion of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research in this area has focused on vibrations of nearly rigid elastic materials. Young et al (2005), for example, excite rectangular and cylindrical Kapton membranes by means of a shaker, and the resulting vibrations and mode shapes are captured using a scanning laser vibrometer. One of the difficulties of conducting dynamic inflation experiments with hyperelastic membranes is the ability to measure the deformation during inflation, as it requires recording displacement data for enough points and with sufficient sampling rates to capture the entire motion of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Young et al (2005), for example, excite rectangular and cylindrical Kapton membrane's by means of a shaker, and the resulting vibrations and mode shapes are captured using a scanning laser vibrometer. One of the difficulties of conducting dynamic inflation experiments with hyperelastic membranes is the ability to measure the deformation during inflation, as it requires recording displacement data for enough points and with sufficient sampling rates to capture the entire motion of the membrane.…”
mentioning
confidence: 99%
“…Membrane theory, fully accounts for geometric non-linearities and hence, non-linear static analysis is being followed by linear model analysis for the rectangular FE membrane model using the prestress along each edge. However, Young et al (2005) showed that vibration modes localized along four edges dominate the dynamics of the rectangular membrane under different tension loads at four corners. The piezo patches (0.02 Â 0.02 Â 0.1e À 2 m 3 ) are attached at the center.…”
Section: Resultsmentioning
confidence: 99%